Efektivitas Alokasi Dana Desa terhadap Pertumbuhan Ekonomi Lokal di Kabupaten Lombok Utara Tahun 2017–2023 - Samudranta, Arya; Adiwikrama, Zhafran (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study examines the effectiveness of Village Fund allocation on local economic growth in North Lombok Regency during the 2017–2023 period. The research is motivated by the strategic role of village fiscal policy in promoting regional economic development, particularly in areas with economic structures dominated by agriculture and community based tourism. The study draws on regional economic growth theory and endogenous growth theory, which emphasize the role of public investment and human capital in increasing regional output. This research employs a quantitative explanatory design. The data consist of panel data covering all villages in North Lombok Regency over a seven year period. The dependent variable is local economic growth, proxied by real regional GDP growth and village per capita income growth. The main independent variable is Village Fund allocation. Control variables include population size, education level, poverty rate, and village capital expenditure. Panel data regression with a fixed effect approach is applied based on the results of the Chow test and Hausman test. The findings indicate that Village Fund allocation has a positive and statistically significant effect on local economic growth at the 5 percent significance level. Increased Village Fund allocation stimulates growth through infrastructure spending and productive village programs. Education level and village capital expenditure also show positive and significant effects, while the poverty rate has a negative impact on economic growth. The coefficient of determination suggests that the model explains a substantial proportion of the variation in village economic growth. The study concludes that Village Fund allocation is effective in promoting local economic growth in North Lombok Regency. However, its effectiveness depends on the quality of budget management and the composition of village spending. Policy optimization should prioritize productive activities and human capital development to ensure more sustainable and inclusive economic growth.